Using Self-reflection in Listening Skills English Proficiency for Teacher Course through Web Source (Universitas Negeri Semarang, 2022)
Self-reflection has been touted as a possible path to work-based learning. However, the goal of this study is to use self-reflection to help B2 and C1 students at the CEFR level enhance their listening skills. This finding is expected to serve as a guide for educators, government officials, corporate leaders, and academics interested in promoting, creating, and implementing self-reflection learning in English listening. This research included two types of analyses. To begin, the writers look at master students in an English proficiency program's self-reflection. Second, the authors look into how people search for self-reflection learning in listening on the internet. The authors specifically employed Google Classroom and web resources to analyze real-world data from 14 students in listening B2 and C1 who completed a listening self-reflection exercise. Students still had some difficulty listening, according to the findings from the study of the identified self-reflection listening assignment. From the perspective of work-based learning, self-reflection has been identified as an important topic in talent development. Self-reflection should be encouraged, created, and implemented by policymakers, educators, researchers, and participants to assist individuals learn on the proper route through valid knowledge and ethical reasoning.